Emotional intelligence effects towards employee intention to stay - Bahyah, Abdul Halim; Natasha Shazleen, Badrul (2015)
This research paper discusses on the relationship between emotional intelligence towards employee intention to stay amongst private higher education institutions. It is a common situation in Malaysia whereby the private higher education institutions faces many challenges including high employee turnover rates and burnout amongst staffs. The data collected represented the private higher education institutions in the East Coast of Malaysia. The respondents for this research are 100 employees who are willingly participated and most of them have a high level of emotional intelligence. They also indicated that they have no intentions of leaving their current job because of their passion and love towards the job. The results shown that employee emotional intelligence significantly have a positive relationship with employee intention to stay.